Pre-Implantation Gender Selection: Family Balancing in Jordan - Sindiani AM; Zayed F; Alshdaifat EH; Rawashdeh HM; Al-Woshah W; Zayed N (Dove Medical Press, 2021)
Amer Mahmoud Sindiani,1 Faheem Zayed,2 Eman Hussein Alshdaifat,3 Hasan M Rawashdeh,1 Wesam Al-Woshah,4 Nada Zayed5 1Department of Obstetrics and Gynecology, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Obstetrics and Gynecology, Irbid Speciality Hospital, Irbid, Jordan; 3Department of Obstetrics and Gynecology, Yarmouk University, Irbid, Jordan; 4Department of Obstetrics and Gynecology, IBN Al-Nafis Hospital, Irbid, Jordan; 5Department of Dermatology, Albalqa Applied University, Salt, JordanCorrespondence: Amer Mahmoud SindianiDepartment of Obstetrics and Gynecology, Faculty of Medicine, Jordan University of Science and Technology, PO Box: 3030, Irbid, 22110, JordanTel +962796025538Email amsindiani0@just.edu.joPurpose: To find out whether couples with predominant female offspring have more chances to produce more female embryos during non-medical pre-implantation genetic diagnosis (PGD) for male sex selection.Methods: A total of 125 couples who had three or more female offspring and underwent non-medical PGD for male sex selection between 2015 and 2019 were included. Nuclear DNA was analyzed by fluorescent in situ hybridization (FISH). Two-chromosome (X, Y), 3-chromosome (21, X, Y), and 5-chromosome (13, 18, 21, X, Y) probes were used for FISH. The standard protocol was followed for sperm processing and embryo culture for IVF and PGD.Results: In 83.2% of the couples, the ratio of female embryos was higher than male embryos. Independent sample t-test showed that there is no significant difference between equal and unequal embryonic groups in patients' age, husbands' age, sperm count, sperm motility, total male embryos, total female embryos, normal male embryos, and normal female embryos. For patients with positive pregnancy outcome, 84.6% had unequal embryonic ratio while 15.4% had equal embryonic ratio. Similarly, patients who were treated by short protocol had 85% of unequal embryonic ratio and 15% had equal ratio.Conclusion: A greater variability in the female to male embryonic ratio is produced in couples having predominantly female offspring and seeking non-medical PGD for male sex selection.Keywords: embryos, infertility, IVF, PGD